Audio Storytelling to Teach Listening Skill for Vocational High School - Astried Damayanti; Sabrina Azaria (STKIP PGRI Trenggalek, 2022)
The objectives this research to know implementation of audio storytelling to teach listening skill in class tenth at SMK Negeri 2 Trenggalek. The research design qualitative research and the type is case study because this research based on phenomenon. This research used two instruments: observation sheet and interview. Observation sheet was used by the researcher to observe the teaching activity and interview was used to find in-depth information by the teacher about the use of storytelling as media in teaching activity. Observation sheet consisted of 6 statements based on techniques of teaching audio storytelling and lesson plan. The findings shows that the implementation of learning using audio story telling in listening has met the criteria expected by the researcher. In interview, researcher gave 6 questions to the teacher. The result shows that audio story telling can be implemented to teach listening skill in tenth grade at SMKN 2 Trenggalek.